CHRONIC CEREBRAL VENOUS DYSFUNCTION SYNDROME AND DEGENERATIVE-DYSTROPHIC CHANGES OF THE CERVICAL SPINE: ANATOMO-PHYSIOLOGICAL UNDERSTANDING OF COMORBIDITY - O. Ye. Kovalenko; N. G. Prytiko (Клінічна та профілактична медицина, 2023)
Aim: to investigate the features of CS DDC in patients with CCVDS in comparison with patients without clinical signs of chronic venous cerebral dysgemia, to substantiate comorbidity.